2019
DOI: 10.3390/medicina55110728
|View full text |Cite
|
Sign up to set email alerts
|

Mature miR-99a Upregulation in the Amniotic Fluid Samples from Female Fetus Down Syndrome Pregnancies: A Pilot Study

Abstract: Background and Objective: Although Down syndrome is the most frequent aneuploidy, its pathogenic molecular mechanisms are not yet fully understood. The aim of our study is to quantify—by qRT-PCR—the expression levels of both the mature forms and the pri-miRNAs of the microRNAs resident on chromosome 21 (miR(21)) in the amniotic fluid samples from Down syndrome singleton pregnancies and to estimate the impact of the differentially expressed microRNAs on Down syndrome fetal heart and amniocytes transcriptomes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Recently, studies have shown that AF provides dynamic ncRNA information about foetal pathophysiological status inside the uterus. Vizitiu et al (2019) showed that miR-99a was significantly upregulated in the AF of foetuses with trisomy 21 syndrome. Xie et al (2017) found that AF-derived miR-299-5p and miR-300 could be used as biomarkers to evaluate foetal kidney function and prenatally diagnose congenital hydronephrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have shown that AF provides dynamic ncRNA information about foetal pathophysiological status inside the uterus. Vizitiu et al (2019) showed that miR-99a was significantly upregulated in the AF of foetuses with trisomy 21 syndrome. Xie et al (2017) found that AF-derived miR-299-5p and miR-300 could be used as biomarkers to evaluate foetal kidney function and prenatally diagnose congenital hydronephrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the miRNA profiling of amniotic fluid was reported, suggesting that miRNAs in the amniotic fluid may contribute to fetal development [42]. The relationship between miRNAs in the amniotic fluid and fetal congenital diseases including chromosomal anomalies has also been investigated [43][44][45]. In chorioamnionitis miR-548, which is highly expressed in the amniotic membrane, alters the inflammatory responses through the regulated expression of HMGB1, and miR-223 and miR-338 are also abundantly expressed in the chorioamniotic membranes [46,47].…”
mentioning
confidence: 99%